Peranan Bidang Hukum Polda Sumbar Sebagai Kuasa Hukum Dalam Menerapkan Mediasi Untuk Penyelesaian Perkara Tindak Pidana - Ruyung Saga; Engrina Fauzi (Jurnal Kajian Hukum Dan Kebijakan Publik | E-ISSN : 3031-8882, 2023)
Article 6 Regulation of the Head of the National Police of the Republic of Indonesia Number 2 of 2017 concerning Procedures for Providing Legal Assistance by the National Police of the Republic of Indonesia. This research is legal research with descriptive analytical specifications and this research uses empirical juridical methods. The role of the West Sumatra Regional Police's Legal Sector as Legal Counsel in Implementing Mediation to Settle Criminal Cases to provide legal assistance and be mediated as a resolution to criminal cases. Legal Sub-Sector with a Letter of Order to the assigned legal advisor/legal representative/companion. The West Sumatra Regional Police Chief provides support through Bidkum Personnel of the West Sumatra Regional Police to provide legal assistance in conducting mediation. The obstacle to the role of the West Sumatra Regional Police's Legal Sector as Legal Attorney in Implementing Mediation to Settle Criminal Cases in the implementation of providing legal assistance by the West Sumatra Regional Police's Legal Sector to members of the National Police who commit criminal acts while carrying out their official duties is a shortage of legal advisors. lack of patience in carrying out the mediation process carried out by members of the police from the legal sub-sector as those involved in the case as well as legal advisors/attorneys/advocates. To the West Sumatra Regional Police in the Legal Sub-sector to increase the number of personnel who have taken the Special Education for the Advocate Profession.